Evaluation of the Hepatoprotective Potential of Silymarin: A Detailed Assessment of Biochemical, Histopathological, and Molecular Mechanisms in Mice Exposed to Acetaminophen-Induced Liver Damage. - Ramasamy, N; Kumar Jain, Sanmati; Ghosh, Balaram; Debnath, Dibyendu; Dutta, Koustav; Kumar Dubey, Preet; Bhowmick, Ananya; Bisht, Shiwali; Patel, Nirali (Journal of Neonatal Surgery, 2025)
Background: Acetaminophen (APAP) overdose is a major cause of drug-induced liver injury (DILI), primarily through the formation of the reactive metabolite N-acetyl-p-benzoquinone imine (NAPQI), which induces oxidative stress and hepatocyte necrosis. Despite the availability of N-acetylcysteine (NAC) as an antidote, limitations such as a narrow therapeutic window necessitate exploration of alternative hepatoprotective agents. Silymarin, a flavonolignan complex from Silybum marianum, is known for its antioxidant, anti-inflammatory, and hepatoprotective properties. Objective: To evaluate the hepatoprotective effects of silymarin against APAP-induced liver injury in mice by analyzing biochemical, histopathological, and molecular parameters. Methods: Male Swiss albino mice were randomly divided into four groups: Control, APAP-treated, Silymarin-treated, and Silymarin + APAP co-treated. Silymarin (100 mg/kg/day) was administered orally for 7 days, and APAP (500 mg/kg, intraperitoneally) was given on day 7. Serum liver enzymes (ALT, AST, ALP, total bilirubin), oxidative stress markers (MDA, GSH, SOD, catalase), histopathology, and gene/protein expression of inflammatory (TNF-α, IL-6, NF-κB), apoptotic (Bcl-2, Bax, Caspase-3), and antioxidant (Nrf2, HO-1) markers were evaluated. Results: APAP significantly elevated liver enzyme levels and oxidative stress markers, disrupted hepatic architecture, and upregulated inflammatory and apoptotic genes while downregulating antioxidant genes (p < 0.01). Co-treatment with silymarin markedly reversed these effects: liver enzyme levels and MDA were reduced, antioxidant markers were restored, and liver histology showed preserved architecture with mild damage. Molecular analysis showed downregulation of TNF-α, IL-6, NF-κB, Bax, and Caspase-3, and upregulation of Bcl-2, Nrf2, and HO-1 in the silymarin + APAP group (p < 0.01 vs. APAP alone). Conclusion: Silymarin confers significant protection against APAP-induced hepatotoxicity through its antioxidant, anti-inflammatory, and anti-apoptotic mechanisms. These findings support silymarin’s potential as a therapeutic agent for managing drug-induced liver injury.